1996
DOI: 10.1002/cber.19961291215
|View full text |Cite
|
Sign up to set email alerts
|

The Interlocking of Salicylic Aldehydes and Ketones with a 2h‐1,2,4,3‐Triazaphosphole

Abstract: Salicylic aldehyde (2a) adds to 2-methyl-5-phenyl-2H-compound forms dimers by a double hydrogen bond bet-1,2,4,3-triazaphosphole (1) to yield the bicyclic phosphonic ween two HN-PO units. Substituted salicylic aldehydes as amide 3a. The OH group adds to the P=N bond, the carbon well as ortho-hydroxyacetophenone and benzophenone reatom of the carbonyl group is inserted into the other P-N act in the same way. bond, and the phosphorus atom is oxidized. In the crystal the The phosphorus atom of a 2H-1,2,4,3-triaza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In recent years, it has been shown that the process in question is more general. Thus, hypophosphorus amides undergo alcoholysis. Interestingly, phosphimine derivatives also react with alcohols and phenols , (Scheme ).
17
…”
Section: General Features Of Phosphorylation Of Alcohols and Phenolsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, it has been shown that the process in question is more general. Thus, hypophosphorus amides undergo alcoholysis. Interestingly, phosphimine derivatives also react with alcohols and phenols , (Scheme ).
17
…”
Section: General Features Of Phosphorylation Of Alcohols and Phenolsmentioning
confidence: 99%
“…Thus, hypophosphorus amides undergo alcoholysis. [141][142][143] Interestingly, phosphimine derivatives also react with alcohols and phenols 144,145 (Scheme 17).…”
Section: General Features Of Phosphorylation Of Alcohols and Phenolsmentioning
confidence: 99%
“…The reaction process was assumed as nucleophilic addition of the hydroxyl group to the P=N bond, the subsequent nucleophilic attack of the nitrogen in 2H-1,2,4,3-triazaphosphole 308 to the carbonyl groups and the generated alkoxide attacking to the phosphorus atom followed by a ring contraction (Scheme 78). [108] Treatment of tri(5-tert-butyl-2-methoxyphenyl)methane (312) with butyl lithium followed by the reaction with ). [109] Reactions of 1-phenyliminobenzo[c] [1,2]oxaphosphole 314 with hexafluoroacetone and phenylisothiocyanate gave the corresponding spirocycloadducts 315 and 318, which underwent thermolysis to generate 3H-benzo[c][1,2]phosphole 1oxide 316 and 1-sulfide 319, respectively, accompanied with imine 317 and carbodiimide 320 (Scheme 80).…”
Section: Miscellaneous Synthesismentioning
confidence: 99%
“…The reaction process was assumed as nucleophilic addition of the hydroxyl group to the P=N bond, the subsequent nucleophilic attack of the nitrogen in 2 H ‐1,2,4,3‐triazaphosphole 308 to the carbonyl groups and the generated alkoxide attacking to the phosphorus atom followed by a ring contraction (Scheme 78). [108] …”
Section: Miscellaneous Synthesismentioning
confidence: 99%